Shortest Path with Dynamic Weight Implementation using Dijkstra’s Algorithm - Elizabeth Nurmiyati Tamatjita; Aditya Wikan Mahastama (Bina Nusantara University, 2016)
Shortest path algorithms have been long applied to solve daily problems by selecting the most feasible route with minimum cost or time. However, some of the problems are not simple. This study applied the case using Dijkstra's algorithm on a graph representing street routes with two possible digraphs: one-way and twoway. Each cost was able to be changed anytime, representing the change in traffic condition. Results show that the usage of one way digraph in mapping the route does make the goal possible to reach, while the usage of twoway digraph may cause confusion although it is probably the possible choice in the real world. Both experiments showed that there are no additional computation stresses in re-calculating the shortest path while going halfway to reach the goal.